Global Value Chain Participation: An Analysis of Key Performance Indicators and Sector Composition of an Emerging Nation (China) and a Developed Nation (Germany) - Milan Lehmkuhl (Hochschule für Angewandte Wissenschaften Hamburg, 2020)
This thesis aims at investigating to what extent, and in which sectors, China’s emerging economy links into Global Value Chains, or GVCs, compared to the patterns of participation of a developed nation such as Germany.